Internal decompression of the acutely contused spinal cord: Differential effects of irrigation only versus biodegradable scaffold implantation. (December 2018) - Guest, James D.; Moore, Simon W.; Aimetti, Alex A.; Kutikov, Artem B.; Santamaria, Andrea J.; Hofstetter, Christoph P.; Ropper, Alexander E.; Theodore, Nicholas; Ulich, Thomas R.; Layer, Richard T.
Abstract: Severe spinal cord injury leads to hemorrhage, edema and elevated tissue pressures that propagate ischemia. Liquefactive necrosis of damaged tissue eventually results in chronic cavities due to a wound healing process lacking adhesive contractile cells. Biomaterials can potently influence wound healing responses. Internal decompression (ID) refers to pial opening, allowing spontaneous extrusion and irrigation of fluid necrotic debris relieving pressure and resulting in a space for biomaterial scaffold insertion. After thoracic contusions, rats were randomized to: contusion only, contusion + ID and contusion + ID + PLGA-PLL scaffold implantation, to test for neuroprotection and endogenous repair over 3 months. ID alone reduced inflammatory activity, cavity volume, and increased tissue sparing. Scaffold biodegradation produced delayed ingrowth of inflammatory and other cells resulting in endogenously derived laminin-rich tissue, marked reduction in cavitation and presence of tissue remodeling macrophages. Extensive recruitment of Schwann cells into adjacent spared white matter occurred, greatest in scaffold-implanted animals. Despite tissue preservation with myelin repair, no groups differed significantly in open field locomotion. However, across all rats, spared epicenter tissue and locomotor outcomes were correlated. Scaffold-implanted animals showed no obvious toxicity. To study the clinical feasibility, timing and indications for scaffold implantation, Göttingen minipigs underwent ID and were implanted with scaffolds 4, 6, and 24 h after T10 contusion. High intra-spinal tissue pressures fell to pre-injury levels after ID and scaffold implantation. Extrusion of necrotic debris left sufficient space for a sized scaffold. These results provided the preclinical rationale for a current clinical study of biomaterial scaffold implantation into the human injured spinal cord. Graphical abstract: The Neuro-Spinal Scaffold promotes new tissue formation . Following contusion, hemorrhagic transformation of grey matter and extension of tissue loss due to secondary injury further destroys grey and white matter, culminating in the formation of a cavity spanned by thin trabeculae. This is a failure of wound healing. Our paradigm proposes that debridement of fluid necro-hemorrhagic debris creates a space into which a biocompatible PLGA-PLL scaffold may be inserted and is subsequently replaced by tissue, reducing or preventing cavitation. This new tissue supported in-migration of Schwann cells, fibroblasts, macrophages, NG2+ cells, axonal growth and myelination.